Future Directions in the Sociology of Non-Institutional Religion - Davidsen, Markus Altena (Implicit religion, 2012)
A shift is taking place in the religious field from collective, institutional, and tradition-bound religion to increasingly individual, non-institutional, and post-traditional religious forms. This article examines how the sociology of religion has responded to this empirical development, paying special attention to two issues to which Meerten Ter Borg has contributed, namely the typologization of the various modes of non-institutional religion and the foundation of non-institutional religion in human nature. I suggest that the sociology of non-institutional religion can advance, particularly if it adopts a substantial definition of religion, opens up for co-operation with cognitive scholars, and turns its attention to religious bricolage, the modes of belief and the effect of the internet on non-institutional religion.